Frailty as a predictor of neurosurgical outcomes in brain tumor patients: A systematic review and meta-analysis - Zhu, Jinfeng; Qiu, Xichenhui; Ji, Cuiling; Wang, Fang; Tao, An; Chen, Lu (Frontiers in Psychiatry, 2023)
Background: The precise relationship between frailty and neurosurgical outcomes in patients with brain tumor has not been established, and thus evidence-based advancements in neurosurgical management. The objectives of this study are to describe existing evidence and conduct the first systematic review and meta-analysis of the relationship between frailty and neurosurgical outcomes among brain tumor patients. Methods: Seven English databases and four Chinese databases were searched to identify neurosurgical outcomes and the prevalence of frailty among patients with a brain tumor, with no restrictions on the publication period. According to the Joanna Briggs Institute (JBI) Manual for Evidence Synthesis and the Preferred Reporting Items for Systematic reviews and Meta-Analysis (PRISMA) guidelines, two independent reviewers employed the Newcastle–Ottawa scale in cohort studies and JBI Critical Appraisal Checklist for Cross-sectional Studies to evaluate the methodological quality of each study. Then random-effects or fixed-effects meta-analysis was used in combining odds ratio (OR) or hazard ratio (RR) for the categorical data and continuous data of neurosurgical outcomes. The primary outcomes are mortality and postoperative complications, and secondary outcomes include readmission, discharge disposition, length of stay (LOS), and hospitalization costs. Results: A total of 13 papers were included in the systematic review, and the prevalence of frailty ranged from 1.48% to 57%. Frailty was significantly associated with increased risk of mortality (OR = 1.63; CI = 1.33–1.98; P ＜ 0.001), postoperative complications (OR = 1.48; CI = 1.40–1.55; P ＜ 0.001; I2 = 33%), nonroutine discharge disposition to a facility other than home (OR = 1.72; CI = 1.41–2.11; P ＜ 0.001), prolonged LOS (OR = 1.25; CI = 1.09–1.43; P = 0.001), and high hospitalization costs among brain tumor patients. However, frailty was not independently associated with readmission (OR = 0.99; CI = 0.96–1.03; P = 0.74). Conclusion: Frailty is an independent predictor of mortality, postoperative complications, nonroutine discharge disposition, LOS, and hospitalization costs among brain tumor patients. In addition, frailty plays a significant potential role in risk stratification, preoperative shared decision making, and perioperative management.